QUESTIONS OF PARTICIPATION IN MASS SPORTS IN THE PROCESS OF TRAINING STUDENTS OF UNIVERSITIES OF KAZAKHSTAN AND TURKEY - Балджы, Велиттин; Ермаханов, Бағлан; Қосшығұлова, Әлия (Pedagogy and Psychology, 2022)
This article talks about the importance of mass sports, the work to support mass sports in the Republic of Kazakhstan and the Republic of Turkey, the goals of the Mass Sports Federation of the Republic of Turkey and the indicators of participation of students of higher educational institutions in mass sports events. The research work was attended by 230 students from the University of Ankara and Haji Bayram Veli, Ankara, and 230 students from the Kazakh National University named after Al-Farabi and the Kazakh National Agrarian University of Almaty. 460 students took part in this article. The scientific article presents the results of a survey of students participating in the research work. The collected data was analyzed in the SPSS program, entered in the form of tables and analyzed.